Positive pole piece and preparation method thereof, secondary battery and electric equipment
By adding an oxygen-suppressing catalyst to the positive electrode sheet, the relationship between A, S, and P is controlled, and oxygen release is suppressed, thus solving the problem of structural collapse of the positive electrode material under high pressure and high temperature, and improving the cycle performance and safety of the battery.
Patent Information
- Application Number
- CN202511594565.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-03
- Publication Date
- 2026-01-30
AI Technical Summary
Under high pressure or high temperature, lattice oxygen activation in the positive electrode layered oxide material leads to oxygen release, which intensifies side reactions, causes structural collapse, results in loss of active ions and increased interfacial impedance, and affects the cycle performance and safety of the battery.
By adding an oxygen-suppressing catalyst to the positive electrode sheet, the mass fraction A, the specific surface area S, and the porosity P of the positive electrode active material are controlled to satisfy the relationship 0.5 < A × S × P / 50 < 1.5, thus inhibiting oxygen release and stabilizing the structure of the positive electrode active material.
It effectively suppresses oxygen release, improves the structural stability of the positive electrode active material, alleviates phase transition problems, and enhances the cycle performance and safety performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery technology, and more specifically, to a positive electrode sheet and its preparation method, a secondary battery, and an electrical device. Background Technology
[0002] Under high pressure or high temperature, the positive electrode layered oxide material undergoes lattice oxygen activation, where lattice oxygen is oxidized to oxygen. Simultaneously, accompanied by side reaction catalysis and material phase transition, the crystal structure decouples from the layered structure, transforming into a spinel / rock salt phase. Transition metal ions migrate into the metal layer, forming dislocations and inert compounds (such as carbonates) on the material surface. Ultimately, this leads to the loss of active ions, capacity decay, and increased interfacial impedance.
[0003] On the other hand, the oxygen released from the cathode material will react with the organic electrolyte to accelerate the decomposition of the SEI film, which will further lead to structural collapse, aggravated side reactions, and even thermal runaway.
[0004] In view of this, the present invention is hereby proposed. Summary of the Invention
[0005] The primary objective of this invention is to provide a positive electrode sheet that, by controlling A, S, and P to satisfy a specific relationship 0.5 < A × S × P / 50 < 1.5, can effectively suppress the oxygen evolution reaction of the positive electrode active material, improve the structural stability of the positive electrode active material, alleviate phase transition problems, and mitigate structural collapse and particle cracking, thereby improving the cycle performance of the battery.
[0006] The second objective of this invention is to provide a method for preparing a positive electrode sheet, in which an oxygen-suppressing catalyst is added during the homogenization process, which can effectively suppress the release of oxygen on the positive electrode side and improve its cycle performance.
[0007] The third objective of this invention is to provide a secondary battery with excellent cycle performance, high energy density, and good safety performance.
[0008] The fourth objective of this invention is to provide an electrical device.
[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: The present invention first provides a positive electrode sheet, which includes a positive current collector and a positive active layer. The positive active layer contains a positive active material, a conductive agent, a binder, and an oxygen-suppressing catalyst. The mass fraction A of the oxygen-suppressing catalyst in the positive active layer, the specific surface area S of the positive active material, and the porosity P of the positive electrode sheet satisfy the following relationship: 0.5 < A × S × P / 50 < 1.5.
[0010] Furthermore, the mass fraction A of the oxygen-suppressing catalyst in the positive electrode active layer is 3% to 7%.
[0011] Furthermore, the specific surface area S of the positive electrode active material is 0.2~0.5m². 2 / g.
[0012] Furthermore, the porosity P of the positive electrode sheet is 20%~50%.
[0013] Furthermore, the oxygen-suppressing catalyst comprises a composite material of transition metal / nitrogen-doped reduced graphene oxide.
[0014] Furthermore, the composite material of transition metal / nitrogen-doped reduced graphene oxide includes at least one of Ni2-N / rGO, Co2-N / rGO, Fe2-N / rGO, Zn-N / rGO, NiCo-N / rGO, and NiMo-N / rGO.
[0015] Furthermore, the battery containing the positive electrode sheet retains ≥90% of its capacity after 300 cycles at 25°C and 1C.
[0016] The present invention further provides a method for preparing the above-mentioned positive electrode sheet, which specifically includes the following steps: mixing positive active material, conductive agent, binder, oxygen-suppressing catalyst and solvent to obtain positive electrode slurry, coating it on the surface of positive current collector, and drying it.
[0017] The present invention also provides a secondary battery, including the above-mentioned positive electrode sheet.
[0018] The present invention also provides an electrical device, including the aforementioned secondary battery.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: by controlling the parameters A, S, and P in the positive electrode to satisfy the specific relationship 0.5 < A × S × P / 50 < 1.5, the present invention can effectively reduce the release of oxygen in the positive electrode, thereby improving the cycle performance of the battery. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0021] Unless otherwise specified, in this invention, terms such as "first aspect," "second aspect," "third aspect," and "fourth aspect" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, terms such as "first," "second," "third," and "fourth" serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0022] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0023] Unless otherwise specified, in this invention, "one or more" or "at least one" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.
[0024] In a first aspect, the present invention provides a positive electrode sheet that suppresses oxygen release, comprising a positive current collector and a positive active layer disposed on at least one surface of the positive current collector.
[0025] The positive electrode active layer contains a positive electrode active material, a conductive agent, a binder, and an oxygen-suppressing catalyst.
[0026] Furthermore, the mass fraction A of the oxygen-suppressing catalyst in the positive electrode active layer, the specific surface area S of the positive electrode active material, and the porosity P of the positive electrode sheet satisfy the following relationship: 0.5 < A × S × P / 50 < 1.5. Wherein, the value of A × S × P / 50 includes, but is not limited to, any one of 0.51, 0.55, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.45, and 1.49, or a range between any two. The unit of the specific surface area S of the positive electrode active material is m². 2 / g.
[0027] The positive electrode provided by this invention can alleviate the oxygen pressure caused by cycling, inhibit the release of oxygen, stabilize the structure of the electrode material, and greatly improve the cycle performance of the battery.
[0028] Specifically, by adding an oxygen-suppressing catalyst to the positive electrode active layer, the oxygen release rate during cycling can be suppressed, thereby improving phase transition issues, enhancing the structural stability of the positive electrode active material, mitigating structural collapse and particle cracking, and significantly improving the battery's cycle performance. However, the content of the oxygen-suppressing catalyst affects battery performance; a higher proportion of the catalyst will significantly reduce the battery's energy density. Therefore, the use of oxygen-suppressing catalysts needs to be carefully coordinated with the cell's cycle performance and energy density requirements to obtain a battery with better overall performance.
[0029] Meanwhile, the specific surface area of the positive electrode active material affects the adsorption state of the oxygen-suppressing catalyst, which in turn affects the final effect on suppressing oxygen release. That is, the binding state of the positive electrode active material with the oxygen-suppressing catalyst is different with different specific surface areas. Forming an oxygen-suppressing catalyst layer with better stability is beneficial to further improving the cycle performance of the battery.
[0030] The porosity of the positive electrode reflects the volume ratio of the pores inside the electrode, which affects the volume of oxygen that can be received on the positive electrode side.
[0031] Therefore, by controlling A, S, and P to satisfy a specific relationship 0.5 < A × S × P / 50 < 1.5, the present invention can effectively suppress the release of oxygen on the positive electrode side, thereby improving the cycle performance of the battery and taking into account high energy density.
[0032] In some specific embodiments, the mass fraction A of the oxygen-suppressing catalyst in the positive electrode active layer is 3% to 7%, including but not limited to any one of 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or any range between two.
[0033] In some specific embodiments, the specific surface area S of the positive electrode active material is 0.2~0.5m². 2 / g, including but not limited to 0.2m 2 / g, 0.25m 2 / g, 0.3m 2 / g, 0.35m 2 / g, 0.4m 2 / g, 0.45m 2 / g, 0.5m 2 The point value of any one of / g or the range value between any two.
[0034] In some specific embodiments, the porosity P of the positive electrode sheet is 20% to 50%, including but not limited to any one of 20%, 25%, 30%, 35%, 40%, 45%, and 50%, or any range between two of them.
[0035] In some specific embodiments, the oxygen-suppressing catalyst comprises a composite material of reduced graphene oxide doped with transition metals and nitrogen (i.e., doped with transition metals and nitrogen). The oxygen-suppressing catalyst can reduce oxygen release from the positive electrode side, reduce phase transitions, and significantly enhance the structural stability of the positive electrode material, thereby achieving a longer cycle life. Specifically, the 3d orbital electrons of the transition metal undergo rearrangement, losing some electrons and becoming positively charged, thus enhancing its electrostatic attraction to O2 molecules.
[0036] In some specific embodiments, the transition metal / nitrogen-doped reduced graphene oxide composite material includes at least one of Ni2-N / rGO, Co2-N / rGO, Fe2-N / rGO, Zn-N / rGO, NiCo-N / rGO, and NiMo-N / rGO. The subscripts in Ni2-N / rGO, Co2-N / rGO, and Fe2-N / rGO represent the atomic ratio of the transition metal to rGO (each 50g of GO corresponds to 2mmol of transition metal).
[0037] In some specific embodiments, the preparation method of the transition metal / nitrogen-doped reduced graphene oxide composite material can employ any method commonly used in the art.
[0038] As an example, the preparation method of NiCo-N / rGO includes: adding 50 mg of graphene oxide (GO) to 100 mL of ethylene glycol (EG) and ultrasonically dispersing for 4 h to obtain a suspension of graphene nanosheets. Then, 1 mmol of CoCl2 and 1 mmol of NiCl2 are dissolved in the above suspension, and ultrasonic treatment is continued for 4 h. Next, under magnetic stirring, 25 mL of hydrazine hydrate solution (N2H4·H2O) containing 1 g of NaOH is added to the suspension. After heating at 120°C for 1 h, the black product is collected with a magnet and then washed repeatedly with water and ethanol several times to obtain NiCo-N / rGO.
[0039] The preparation methods for Ni2-N / rGO, Co2-N / rGO, Fe2-N / rGO, Zn-N / rGO, and NiMo-N / rGO are similar, except that the corresponding transition metal raw materials are replaced. For example, Ni2-N / rGO is prepared using 2 mmol of NiCl2, Co2-N / rGO using 2 mmol of CoCl2, Fe2-N / rGO using 2 mmol of FeCl2, Zn-N / rGO using 1 mmol of ZnCl2, and NiMo-N / rGO using 1 mmol of NiCl2 and 1 mmol of MoCl2.
[0040] In some specific embodiments, the battery containing the positive electrode sheet exhibits a capacity retention rate of ≥90% after 300 cycles at 25°C and 1C, including but not limited to point values or ranges between any one of 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, and 98%. The discharge capacity retention rate during the 1C charge-discharge cycle reflects the capacity decay of the battery cell and measures the stability of the CEI (Cycle Integrity Index) of both the positive and negative electrode sheets.
[0041] In some specific embodiments, the positive electrode active material includes any positive electrode material commonly used in the art, such as lithium-containing layered oxide positive electrode material, sodium-containing layered oxide positive electrode material, etc., but is not limited thereto.
[0042] In some specific embodiments, the conductive agent includes any conductive reagent commonly used in the art, such as conductive carbon black, conductive graphite, carbon nanotubes, graphene, etc., wherein conductive carbon black includes conductive carbon black SP (super P), acetylene black (AB), Ketjen black (KB), etc., but is not limited to these.
[0043] In some specific embodiments, the adhesive may be any adhesive material commonly used in the art, such as carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), waterborne adhesive, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc., but is not limited thereto.
[0044] Secondly, the present invention provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps: mixing positive active material, conductive agent, binder, oxygen-suppressing catalyst and solvent evenly to obtain a positive electrode slurry; coating the positive electrode slurry on the surface of a positive current collector, and then drying it to obtain a positive electrode sheet.
[0045] To suppress the oxygen evolution reaction of the positive electrode active material, this invention adds an oxygen-suppressing catalyst during the homogenization process. This catalyst can alleviate the oxygen release pressure, improve the structural stability of the positive electrode active material, and thus improve the overall cycle performance of the battery cell.
[0046] In some specific implementations, the positive current collector includes, but is not limited to, aluminum foil.
[0047] In some specific implementations, NMP may be used as the solvent, but it is not limited to this.
[0048] Thirdly, the present invention provides a secondary battery comprising the aforementioned positive electrode sheet.
[0049] This secondary battery exhibits excellent cycle performance, high energy density, and good safety performance.
[0050] In some specific implementations, the secondary battery includes, but is not limited to, sodium-ion batteries and lithium-ion batteries.
[0051] In some specific implementations, the secondary battery also includes a negative electrode, a separator, and an electrolyte.
[0052] In some specific embodiments, the negative electrode sheet includes a negative current collector and a negative active layer. The negative active layer contains a negative active material, a conductive agent, and a binder. The negative active material includes any active material commonly used in the art, such as amorphous carbon materials, titanium-based materials, alloy materials, organic negative electrode materials, etc., but is not limited to these.
[0053] In some specific embodiments, the electrolyte is an organic solvent containing sodium salts, including sodium hexafluorophosphate, sodium perchlorate, etc., and the organic solvents include EC, DMC, EMC, etc.
[0054] In some specific embodiments, the diaphragm includes polyethylene (PP) diaphragm, polypropylene (PE) diaphragm, etc., but is not limited to these.
[0055] Fourthly, the present invention provides an electrical device including the aforementioned secondary battery.
[0056] The electrical equipment used in this invention is not particularly limited and may include, but is not limited to, the following types: laptops, pen-based computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, and large household batteries, etc.
[0057] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0058] Example 1 The method for preparing the positive electrode sheet provided in this embodiment includes the following steps: Na, the positive electrode active material 2 / 3 Cu 1 / 3 Mn 2 / 3 O2 (its specific surface area S is 0.3120 m²) 2A mixture of conductive carbon black SP (superP), polyvinylidene fluoride (PVDF), and oxygen-suppressing catalyst Ni2-N / rGO was uniformly mixed in a ratio of 87%:5%:5%:3% (by mass percentage), and a solvent was added to obtain a positive electrode slurry. The positive electrode slurry was coated onto both surfaces of an aluminum foil and dried to obtain a positive electrode sheet with a porosity P of 31.2%.
[0059] The preparation method of the oxygen-suppressing catalyst Ni2-N / rGO is as follows: 50 mg of graphene oxide (GO) was added to 100 mL of ethylene glycol (EG) and ultrasonically dispersed for 4 h to obtain a suspension of graphene nanosheets. Then, 2 mmol of NiCl2 was dissolved in the above suspension, and ultrasonic treatment was continued for 4 h. Next, under magnetic stirring, 25 mL of hydrazine hydrate solution (N2H4·H2O) containing 1 g of NaOH was added to the suspension. After heating at 120°C for 1 h, the black product was collected with a magnet and then washed repeatedly with water and ethanol several times.
[0060] Example 2 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode active material Na is used... 2 / 3 Cu 1 / 3 Mn 2 / 3 The mass percentages of O2, conductive carbon black SP, polyvinylidene fluoride and oxygen-suppressing catalyst Ni2-N / rGO are replaced with 85%:5%:5%:5%.
[0061] Example 3 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode active material Na is used... 2 / 3 Cu 1 / 3 Mn 2 / 3 The mass percentages of O2, conductive carbon black SP, polyvinylidene fluoride, and oxygen-suppressing catalyst Ni2-N / rGO are replaced with 84%:5%:5%:6%.
[0062] Example 4 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 1, except that: the positive electrode active material Na is used... 2 / 3 Cu 1 / 3 Mn 2 / 3 The mass percentages of O2, conductive carbon black SP, polyvinylidene fluoride, and oxygen-suppressing catalyst Ni2-N / rGO are replaced with 83%:5%:5%:7%.
[0063] Example 5 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 2, the only difference being: the positive electrode active material Na 2 / 3 Cu1 / 3 Mn 2 / 3 The specific surface area S of O2 is 0.2090 m². 2 / g.
[0064] Example 6 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 2, the only difference being: the positive electrode active material Na 2 / 3 Cu 1 / 3 Mn 2 / 3 The specific surface area S of O2 is 0.4290 m². 2 / g.
[0065] Example 7 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in embodiment 2, except that the porosity P of the positive electrode sheet is controlled to be 19.8%.
[0066] It is understandable that the porosity P of the positive electrode sheet can be controlled by adjusting the ambient humidity and temperature during the coating stage, as well as the coating surface density and coating speed.
[0067] Example 8 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in embodiment 2, except that the porosity P of the positive electrode sheet is controlled to be 41.2%.
[0068] Example 9 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in embodiment 2, except that the porosity P of the positive electrode sheet is controlled to be 47.5%.
[0069] Example 10 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 2, except that Ni2-N / rGO is replaced with an equal mass of Co2-N / rGO.
[0070] The preparation method of the oxygen-suppressing catalyst Co2-N / rGO is as follows: 50 mg of graphene oxide (GO) was added to 100 mL of ethylene glycol (EG) and ultrasonically dispersed for 4 h to obtain a suspension of graphene nanosheets. Then, 2 mmol of CoCl2 was dissolved in the above suspension, and ultrasonic treatment was continued for 4 h. Next, under magnetic stirring, 25 mL of hydrazine hydrate solution (N2H4·H2O) containing 1 g of NaOH was added to the suspension. After heating at 120°C for 1 h, the black product was collected with a magnet and then washed repeatedly with water and ethanol several times.
[0071] Example 11 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 2, except that Ni2-N / rGO is replaced with an equal mass of Fe2-N / rGO.
[0072] The preparation method of the oxygen-suppressing catalyst Fe2-N / rGO is as follows: 50 mg of graphene oxide (GO) was added to 100 mL of ethylene glycol (EG) and ultrasonically dispersed for 4 h to obtain a suspension of graphene nanosheets. Then, 2 mmol of FeCl2 was dissolved in the above suspension, and ultrasonic treatment was continued for 4 h. Next, under magnetic stirring, 25 mL of hydrazine hydrate solution (N2H4·H2O) containing 1 g of NaOH was added to the suspension. After heating at 120°C for 1 h, the black product was collected with a magnet and then washed repeatedly with water and ethanol several times.
[0073] Example 12 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 2, except that Ni2-N / rGO is replaced with an equal mass of Zn-N / rGO.
[0074] The preparation method of the oxygen-suppressing catalyst Zn-N / rGO is as follows: 50 mg of graphene oxide (GO) was added to 100 mL of ethylene glycol (EG) and ultrasonically dispersed for 4 h to obtain a suspension of graphene nanosheets. Then, 1 mmol of ZnCl2 was dissolved in the above suspension, and ultrasonic treatment was continued for 4 h. Next, under magnetic stirring, 25 mL of hydrazine hydrate solution (N2H4·H2O) containing 1 g of NaOH was added to the suspension. After heating at 120°C for 1 h, the black product was collected with a magnet and then washed repeatedly with water and ethanol several times.
[0075] Example 13 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 2, except that Ni2-N / rGO is replaced with an equal mass of NiCo-N / rGO.
[0076] The preparation method of the oxygen-suppressing catalyst NiCo-N / rGO is as follows: 50 mg of graphene oxide (GO) was added to 100 mL of ethylene glycol (EG) and ultrasonically dispersed for 4 h to obtain a suspension of graphene nanosheets. Then, 1 mmol of CoCl2 and 1 mmol of NiCl2 were dissolved in the above suspension, and ultrasonic treatment was continued for 4 h. Next, under magnetic stirring, 25 mL of hydrazine hydrate solution (N2H4·H2O) containing 1 g of NaOH was added to the suspension. After heating at 120°C for 1 h, the black product was collected with a magnet and then washed repeatedly with water and ethanol several times.
[0077] Example 14 The preparation method of the positive electrode sheet provided in this embodiment is basically the same as that in Example 2, except that Ni2-N / rGO is replaced with an equal mass of NiMo-N / rGO.
[0078] The preparation method of the oxygen-suppressing catalyst NiMo-N / rGO is as follows: 50 mg of graphene oxide (GO) was added to 100 mL of ethylene glycol (EG) and ultrasonically dispersed for 4 h to obtain a suspension of graphene nanosheets. Then, 1 mmol of NiCl2 and 1 mmol of MoCl2 were dissolved in the above suspension, and ultrasonic treatment was continued for 4 h. Next, under magnetic stirring, 25 mL of hydrazine hydrate solution (N2H4·H2O) containing 1 g of NaOH was added to the suspension. After heating at 120°C for 1 h, the black product was collected with a magnet and then washed repeatedly with water and ethanol several times.
[0079] Comparative Example 1 The preparation method of the positive electrode sheet provided in this comparative example is basically the same as that in Example 1, except that: the positive electrode active material Na is used... 2 / 3 Cu 1 / 3 Mn 2 / 3 The mass percentages of O2, conductive carbon black SP, polyvinylidene fluoride and oxygen-suppressing catalyst Ni2-N / rGO are replaced with 88%:5%:5%:2%.
[0080] Comparative Example 2 The preparation method of the positive electrode sheet provided in this comparative example is basically the same as that in Example 1, except that: the positive electrode active material Na is used... 2 / 3 Cu 1 / 3 Mn 2 / 3 The mass percentages of O2, conductive carbon black SP, polyvinylidene fluoride, and oxygen-suppressing catalyst Ni2-N / rGO are replaced with 82%:5%:5%:8%.
[0081] Comparative Example 3 The preparation method of the positive electrode sheet provided in this comparative example is basically the same as that in Example 2, the only difference being: the positive electrode active material Na 2 / 3 Cu 1 / 3 Mn 2 / 3 The specific surface area S of O2 is 0.0970 m². 2 / g.
[0082] Comparative Example 4 The preparation method of the positive electrode sheet provided in this comparative example is basically the same as that in Example 2, the only difference being: the positive electrode active material Na 2 / 3 Cu 1 / 3 Mn 2 / 3 The specific surface area S of O2 is 0.5120 m². 2 / g.
[0083] Comparative Example 5 The preparation method of the positive electrode sheet provided in this comparative example is basically the same as that in Example 2, except that the porosity P of the positive electrode sheet is controlled to be 9.5%.
[0084] Comparative Example 6 The preparation method of the positive electrode sheet provided in this comparative example is basically the same as that in Example 2, except that the porosity P of the positive electrode sheet is controlled to be 67.5%.
[0085] The mass fraction A of the oxygen-suppressing catalyst in the positive electrode active layer, the specific surface area S of the positive electrode active material, the porosity P of the positive electrode sheet, and the value of A×S×P / 50 in each embodiment and comparative example are shown in Table 1.
[0086] The method for testing the porosity P of the positive electrode sheet is as follows: A positive electrode sheet of a certain mass m0 is cut, its volume V is calculated, and it is immersed in an electrolyte with density ρ. After immersion for 24 hours, the positive electrode sheet is removed and wiped with filter paper until a constant weight is obtained, yielding the mass m1 of the positive electrode sheet. The porosity P of the positive electrode sheet is calculated using the formula P = (m1 - m0) / ρV × 100%.
[0087] It is understood that, since the preparation methods of each embodiment are different, the porosity P of the positive electrode sheet prepared in each embodiment is also different.
[0088] Experimental Example The positive electrode sheets prepared in each embodiment and each comparative example were assembled into batteries and subjected to cycle performance tests. The test results are shown in Table 1.
[0089] The battery is prepared as follows: Hard carbon (a negative electrode active material), a conductive agent (Super P), and a binder (CMC and SBR in a 1:1 mass ratio) are uniformly mixed in a 90%:5%:5% mass percentage ratio, and a solvent is added to obtain a negative electrode slurry. The negative electrode slurry is coated onto aluminum foil and dried to obtain a negative electrode sheet. A tab bonding process is performed on the positive and negative electrode sheets. After the positive electrode sheet, separator, and negative electrode sheet are wound together, a baking process is performed to remove moisture, and then they are encapsulated in an aluminum-plastic film. Electrolyte is then injected and sealed. The battery is then activated by capacity testing to obtain an electrochemically active sodium-ion battery. The electrolyte is a 1 mol / L sodium salt NaPF6 (sodium hexafluorophosphate) dissolved in a 1:1 volume ratio of EC (ethylene carbonate) and PC (propylene carbonate), and the separator is a polyethylene (PP) separator.
[0090] The test method for cycle performance is as follows: charge and discharge tests are conducted at room temperature (25°C) with a current density of 1C. The percentage of the discharge capacity of each cycle to the discharge capacity of the second cycle is defined as the capacity retention rate. The capacity retention rate after 300 cycles is used as the standard for judging the quality of cycle performance (greater than 90% is considered superior performance).
[0091] Table 1 Key parameters of the positive electrode and test results of battery cycle performance
[0092] As shown in Table 1, the positive electrode sheets prepared in each embodiment all satisfy the relationship 0.5 < A × S × P / 50 < 1.5, and have excellent cycle performance.
[0093] However, the positive electrode sheets prepared in each ratio do not satisfy the relationship 0.5 < A × S × P / 50 < 1.5, and the cycle performance is significantly reduced.
[0094] As can be seen, by controlling A, S, and P to satisfy the specific relationship 0.5 < A × S × P / 50 < 1.5, the present invention can effectively suppress the oxygen evolution reaction of the positive electrode active material, thereby significantly improving the cycle performance of the battery.
[0095] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.
Claims
1. A positive electrode sheet, characterized by, The positive electrode active layer contains a positive electrode active material, a conductive agent, a binder, and an oxygen-suppression catalyst. The mass fraction A of the oxygen-suppression catalyst in the positive electrode active layer, the specific surface area S of the positive electrode active material, and the porosity P of the positive electrode sheet satisfy the following relationship: 0.5 < A x S x P / 50 < 1.
5.
2. The positive electrode sheet according to claim 1, characterized by The mass fraction A of the oxygen-suppression catalyst in the positive electrode active layer is 3% to 7%.
3. The positive electrode sheet according to claim 1, wherein The specific surface area S of the positive electrode active material is 0.2 to 0.5 m 2 / g.
4. The positive electrode plate of claim 1, wherein, The porosity P of the positive electrode sheet is 15% to 50%.
5. The positive electrode plate of claim 1, wherein, The oxygen-suppression catalyst comprises a transition metal / nitrogen-doped reduced graphene oxide composite.
6. The positive electrode sheet according to claim 5, wherein The transition metal / nitrogen-doped reduced graphene oxide composite comprises at least one of Ni2-N / rGO, Co2-N / rGO, Fe2-N / rGO, Zn-N / rGO, NiCo-N / rGO, and NiMo-N / rGO.
7. The positive electrode sheet according to any one of claims 1 to 6, wherein The battery containing the positive electrode sheet has a capacity retention rate ≥ 90% after 300 cycles at 25°C and 1C.
8. The method of producing a positive electrode sheet according to any one of claims 1 to 7, wherein The method comprises the following steps: mixing a positive electrode active material, a conductive agent, a binder, an oxygen-suppression catalyst, and a solvent to obtain a positive electrode slurry, coating the positive electrode slurry on the surface of a positive electrode current collector, and drying.
9. A secondary battery characterized by comprising: The positive electrode sheet comprises the positive electrode sheet according to any one of claims 1 to 7.
10. An electric device, characterized by The secondary battery comprises the secondary battery according to claim 9.
Citation Information
Patent Citations
Positive plate and battery
CN117038853A
Lithium-rich composite material and preparation method and application thereof
CN117059791A